Subcutaneous and muscular metastasis of the colorectal cancer on F-18 FDG PET/CT - Savaş Karyağar; Uğur Kesici; Sevda Karyağar; Can Kece; Ali Güner; Güray Duman; Uzel Küçütulu (Turkish Journal of Gastroenterology, 2019)
-